(untitled) (Borneo Engineering & Advanced Multidisciplinary International Journal, 2022)
This project proposes a smart lighting system based on human presence. Pyroelectric Infrared (PIR Sensor) will be utilized to detect the human presence and the Light Dependent Resistor (LDR Sensor) will be used to measure the surrounding light intensity which will manage to fix the lamp light based on the surrounding light intensity. The dimmer principle is based on Pulse Width Modulation (PWM) which will control the light intensity. In this system dual modes are used, which is auto and manual modes. In the manual mode, the system will be controlled using mobile app which will be connected through Bluetooth to the system. Meanwhile, for auto mode, the system will operate based on the human presence in the place.